Analysis of Manual Material Handling Technique and Its Association with Low Back Pain (LBP) Among Fisherman In Kangkung Village, Bandar Lampung - Mayasari, D; Saftarina, F; Indah Sari, M; Sirajudin, A (KnE Life Sciences, 2019)
Low Back Pain (LBP) is a sensation of pain in the lower back that may derive from the spine, muscle, nerve, and other structures around the area. Factors that possibly contribute to LBP are including individual factors, occupational factors, and environmental factors. Manual material handling (MMH) is still unavoided to do a job as a fisherman, especially in Kankung Village. Our preliminary study found that 9 of 10 fishermen in Kangkung Village had a complaint of pain at the lower back of the body. This study aimed to determine the association between MMH technique, age, body mass index (BMI), work period, load mass and lifting frequency with the occurrence of LBP. This research was an observational study with a cross-sectional design, involving 101 subjects which were taken by consecutive sampling technique. Data were collected by interview and physical examination using the Lasseque test to determine LBP. Independent variables were age, BMI, MMH technique, work period, load mass and lifting frequency. The dependent variable was LBP. Data were analyzed with Chi-square test (α=0.05). Prevalence of LBP among fisherman in Kangkung Village was 81.2%. There was a significant association between age (p= 0.001), BMI (p= 0.011), MMH technique (p= 0.003), work period (p= 0.001), load mass (p= 0.001), lifting frequency (p=0.012) with the occurrence of LBP. Age, BMI, work period, MMH technique, load mass, and lifting frequency are the risk factor of LBP among fisherman. An ergonomic work procedure is urgently applied to prevent LBP. Keywords: fisherman, low back pain, manual material handling